More Competitiveness of the Port of Koper Through Supply Chain Integration - Trupac, Igor; Twrdy, Elen (Promet - Traffic&Transportation, 2012)
With the European Union growing eastwards and with the establishment of important production facilities in the countries of Central and Eastern Europe, the hinterland potential is bound to grow even more. The strategic goal of the Port of Koper is to become one of the best ports in the Southern Europe, to develop from a handling port into a commodity distributional centre. Penetrating and exploiting these markets demands cooperation (integration) with the existing inland terminals (logistic centres) and establishing of new ones positioned between Eastern and Western Europe.This paper aims to present and analyse: (I) supply chains of the flow of goods through the Port of Koper to/from the countries of Central and Eastern Europe, (II) the current state and strategies to optimize the flow of goods, (III) market potential, investments in new terminals and capacities.KEY WORDS: Port of Koper, strategies, goals, supply chains, integration, new terminals, market potential, investments